Barriers to and Support for Physical Activity in Overweight and Obese Compared with Normal Weight Adolescents - A. Azadi; M. Anoosheh; F. Alhani; E. Hajizadeh (Iran University of Medical Sciences, 2007)
Introduction and Aim: As the prevalence of overweight increases among adolescents, thus factors that may influence children's participation in weight-related health behaviors need to be examied. This study examined barriers to and support for physical activity in overweight and obese adolescents compared with normal weight adolescents. Materials and Methods: In this cross-sectional study, sample included 279 male students studying in two secondary schools in Tehran. Of all students , 179 (64.2%) were within normal weight range, 49(17.6%) were obese and 51(18.3%) were overweight. A questionnaire comprising demographic characteristics, and barriers to and support for physical activity, and also, a checklist of physical activity within current week were distributed to be filled out by students. Data were analyzed using One-Way ANOVA and Tukey's test.   Results: According to finding, adolescents with normal weight had significantly higher moderate and vigorous physical activity than obese adolescents and the time of TV watching were significantly more among overweight and obese adolescents than adolescents with normal weight. Body-related, social and fitness barriers were the most predominant ones among obese adolescents. There was no statistically significant difference between mean score of convenience and resource barriers among different weight groups. Obese adolescents also reported significantly lower levels of adult and peer support for physical activity. Conclusion: Obese adolescents may be particularly vulnerable to body-related, social and fitness barriers to physical activity. Reducing these barriers may be helpful, as physical activity intervention is most relevant for overweight youth. Interventions should be implemented for reducing barriers to physical activity and also enhancing parents and peers support for physical activity among obese adolescents.